2010
DOI: 10.1152/ajpgi.00193.2010
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of aberrant transient receptor potential cation channel, subfamily V, member 6 expression in hyperproliferative colonic crypts by dietary calcium

Abstract: Dietary calcium is believed to reduce colon cancer risk, but the mechanism by which this occurs is poorly understood. Employing the Citrobacter rodentium-induced transmissible murine colonic hyperplasia (TMCH) model, we previously showed that a high-calcium diet (hCa) significantly abrogated hyperplasia in the distal colons of NIH-Swiss mice. Here, we explored the mechanism of dietary protection by hCa by analyzing the expression of genes involved in the regulation of Ca uptake/flux in the intestinal epitheliu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 40 publications
2
30
0
Order By: Relevance
“…The link between TRPV6 and NFAT activity was also reported in the human colon carcinoma Caco-2 cells [41]. It is known that NFAT interacts with calcium-signaling.…”
Section: Discussionmentioning
confidence: 61%
“…The link between TRPV6 and NFAT activity was also reported in the human colon carcinoma Caco-2 cells [41]. It is known that NFAT interacts with calcium-signaling.…”
Section: Discussionmentioning
confidence: 61%
“…It has previously been shown that mice treated with high-dose 1,25(OH) 2 D 3 (75 ng, 3 times/wk) developed exaggerated crypt hyperplasia at day 12 postinfection with C. rodentium; however, other aspects of disease were not reported (54). We found that 1,25(OH) 2 D 3 -treated infected mice suffered from increased C. rodentium burdens and exag- gerated colonic tissue damage, compared with vehicle-treated mice.…”
Section: Discussionmentioning
confidence: 98%
“…Since hyper-activation of Wnt signaling is a hallmark of colon cancer and of many other human cancers, our findings clearly suggest that the TMCH model can be used as an excellent template to study the early stages of colon carcinogenesis. Indeed, we have shown recently that following CR infection, aberrant overexpression of a calcium channel TRPV6 (transient receptor potential vanilloid-type) contributes to colonic crypt hyperplasia in mice and to colon cancer cell proliferation in humans [97]. Blocking TRPV6 with high calcium diet (1%) causes almost complete abrogation of hyperplasia.…”
Section: Introductionmentioning
confidence: 99%
“…As proof of principle, we also investigated TRPV6 expression in adenomatous polyps (stage I) and advanced human cancers (stages III/IV) to determine if similarities exist with regard to TMCH model. A significant increase in TRPV6 expression, compared to normal mucosa, was observed in stage I tumor while stages III and IV cancers were negative for TRPV6 thus linking TRPV6 to early stages of colon cancer [97]. The remarkable parallel with TMCH also suggests that TMCH is not unique but shares a common final pathway in response to diverse initiating events.…”
Section: Introductionmentioning
confidence: 99%